2009
DOI: 10.5194/acp-9-7313-2009
|View full text |Cite
|
Sign up to set email alerts
|

Error correlation between CO<sub>2</sub> and CO as constraint for CO<sub>2</sub> flux inversions using satellite data

Abstract: Abstract. Inverse modeling of CO 2 satellite observations to better quantify carbon surface fluxes requires a chemical transport model (CTM) to relate the fluxes to the observed column concentrations. CTM transport error is a major source of uncertainty. We show that its effect can be reduced by using CO satellite observations as additional constraint in a joint CO 2 -CO inversion. CO is measured from space with high precision, is strongly correlated with CO 2 , and is more sensitive than CO 2 to CTM transport… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 69 publications
0
39
1
Order By: Relevance
“…On the other hand, the large random error in the individual measurements could be an issue for inverse modeling. For example, Wang et al (2009) showed that a joint inversion analysis of CO and CO 2 , exploiting the correlations in the model errors for CO and CO 2 would provide more constraints on the CO 2 fluxes than using only CO 2 . But a requirement of joint inversion approach, as noted by Wang et al (2009), is that the measurement error must be smaller than the model error.…”
Section: Inversion Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the large random error in the individual measurements could be an issue for inverse modeling. For example, Wang et al (2009) showed that a joint inversion analysis of CO and CO 2 , exploiting the correlations in the model errors for CO and CO 2 would provide more constraints on the CO 2 fluxes than using only CO 2 . But a requirement of joint inversion approach, as noted by Wang et al (2009), is that the measurement error must be smaller than the model error.…”
Section: Inversion Resultsmentioning
confidence: 99%
“…For example, Wang et al (2009) showed that a joint inversion analysis of CO and CO 2 , exploiting the correlations in the model errors for CO and CO 2 would provide more constraints on the CO 2 fluxes than using only CO 2 . But a requirement of joint inversion approach, as noted by Wang et al (2009), is that the measurement error must be smaller than the model error. A more detailed analysis is clearly needed to better assess the potential impact of the spatial and temporal averaging of the data on the inferred flux estimates.…”
Section: Inversion Resultsmentioning
confidence: 99%
“…However, this analysis suggests that CO might be a useful transport tracer for placing constraints on total methane emissions as demonstrated for CO 2 fluxes (e.g., Palmer et al, 2006;Wang et al, 2009). Alternatively, observations in the change of the slope of the CH 4 /CO distribution over "short" time periods might provide constraints on biomass burning over this region if we assume that non-fire emissions remain approximately constant over the "short" time period.…”
Section: South Americamentioning
confidence: 99%
“…The operational retrieval for TROPOMI is described by , who find that the precision is almost always better than 1 % and that over 90 % of cloud-free scenes can be successfully retrieved. Observations of methane-CO corre-lations from joint 2.3 µm retrievals may provide useful additional information for inferring methane sources (Xiao et al, 2004;Wang et al, 2009;Worden et al, 2013).…”
Section: Tir Swirmentioning
confidence: 99%
“…TROPOMI will provide data for both methane and CO from common SWIR retrievals. Beyond constraining the combustion source of methane, the CO observations could be valuable for decreasing model transport errors in joint methane-CO inversions (Wang et al, 2009). …”
Section: Applications To Sciamachy and Gosat Datamentioning
confidence: 99%